THE ROLE OF TRAINING CURRICULUM SUPERVISED TRAINING OF STUDENTS IN PHYSICAL EDUCATION IN THE CARIRI REGION. (Fiep Bulletin - online, 2010)
Internships are seen as a process of professional preparation and as a means of knowledge responsible for the integration of theory with practice, present in the construction and acquisition of knowledge. From this premise we decided to investigate the role of supervised internships for undergraduate courses of Bachelor of Physical Education in the IES Cariri. This research is characterized as descriptive, a fieldwork and qualitative. The sample comprised 49 participants (23 males and 26 females). The instrument used was the Questionnaire About Supervised Curricular Course for Academic Degree in Physical Education (adapted from Winch et al, 2006). The data were divided into blocks and analyzed qualitatively through content analysis. Analyzing the block I (Role of supervised curriculum), it was noted that for most, the stage has key role in professional preparation. As for Block II (Preparation of the trainee for the development stage), we found that for students the institution has prepared about the development of internships, but they do not feel fully prepared to initiate and develop the same. Analyzing the Block III (Expectation of trainees regarding supervised curricular), revealed a number of anxieties on the part of students and the completion of stages, demonstrating the need for more support from the IHE and schools of basic education. It follows therefore that there is a lack of link between medical schools and schools of basic education, making it difficult to grip the trainees to it. It is necessary a greater commitment of both, so that these stages become important vehicles in academia, can contribute in enabling their inclusion in the labor market in a homogeneous way
Keywords: Internship; Physical Education; Graduates